A Quasi‐Two‐Dimensional Copper Based Organic‐Inorganic Hybrid Perovskite with Reversible Thermochromism and Ferromagnetism. Issue 47 (17th November 2021) - Fu, Hanmei; Jiang, Chunli; Luo, Chunhua; Lin, Hechun; Peng, Hui
Abstract: Two‐dimensional (2D) organic‐inorganic hybrid perovskites (OHPs) have been gaining more and more attention for their unique optical, electrical and magnetic behaviors. Herein, we report a multifunctional quasi‐2D hybrid perovskite, 1, 6‐hexanediammonium tetrachlorocuprate ((1, 6‐HDA)CuCl4 ), which exhibit reversible thermochromic behavior, temperature‐dependent conductivity and ferromagnetism. Changing temperature results in the reversible color change of (1, 6‐HDA)CuCl4 between yellow and brown. A screen‐printing ink is prepared by using (1, 6‐HDA)CuCl4 and used to print thermochromic patterns. The reversible thermochromism originates from the CuCl6 octahedron distortions and lattice expansion in the crystal structure. The conductivity varies more than two orders of magnitude upon temperature change. (1, 6‐HDA)CuCl4 also shows ferromagnetic property with Curie temperatures around 12 K. Abstract : A stable quasi‐two‐dimensional copper perovskite, 1, 6‐hexanediammonium tetrachlorocuprate ((1, 6‐HDA)CuCl4 ), is successfully synthesized, which consists of alternating [1, 6‐HDA] 2+ cations layers and CuCl6 octahedrons layers, and shows reversible thermochromism and ferromagnetism.